Review on multi-stage incremental forming process to form vertical walled cup. (2020) - Vignesh, G.; Pandivelan, C.; Sathiya Narayanan, C.
Abstract: Using incremental forming, forming of a vertical walled cup was impossible in a single-stage due to the reason that failure is followed by thinning at transition region (in between the wall & base of the cup). However in the recent years, forming of a cup with vertical wall or maximum wall angle compared to Single-stage Single Point Incremental Forming (SPIF) are being done successfully by many researchers using Multi-stage Single Point Incremental Forming (MSPIF) process. The reason behind the implementation of MSPIF process is that the thinning will be postponed even when the maximum wall angle is achieved, with number of intermediate stages during Incremental Forming. In the case of Single-stage Incremental Forming, wall angle beyond a certain limit can't be obtained due to the reason that thinning will occur suddenly at transition region. In this paper, a review is presented on MSPIF process to form cup with vertical wall or maximum wall angle compared to Single-stage Incremental Forming. In addition, tool path design, different forming strategies, effect of forming direction & strategy, Rigid Body Translation (RBT) during intermediate stages, geometrical accuracy of formed part such as dimensional deviation & step formation at base, Formability using Forming Limit Stress Diagram (FLSD) and Thickness distribution and comparisons of MSPIF process are discussed. Further, works proposed for future to improve the process is also presented in this paper.